2022
DOI: 10.1080/21655979.2022.2056690
|View full text |Cite
|
Sign up to set email alerts
|

Echinococcus multilocularis drives the polarization of macrophages by regulating the RhoA-MAPK signaling pathway and thus affects liver fibrosis

Abstract: Echinococcus multilocularis is a small parasite that causes alveolar echinococcosis. It primarily induces liver disorder, such as liver fibrosis and even liver cancer, which severely endangers human lives. This study aims to explore the efficacy of Echinococcus multilocularis soluble antigen in preventing and alleviating alveolar echinococcosis-induced liver fibrosis and determine the underlying mechanism. We first identified the optimal dose and time of Echinococc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…CD206 + macrophages have been described to promote angiogenesis and produce chemokines supporting tumor growth ( 29 , 30 ). AE was shown to be associated with periparasitic accumulation of monocyte-derived M1 macrophages during the early phase of infection, which acquire a M2 phenotype (CD206 + ) during the chronic stage of infection ( 31 , 32 ). These macrophages are considered to favor parasite growth because they secrete the anti-inflammatory cytokine IL-10 and the fibrogenic cytokine TGF-β1, which has a dual role: slowing the parasite growth on one hand, and having immunosuppressive properties on the other ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD206 + macrophages have been described to promote angiogenesis and produce chemokines supporting tumor growth ( 29 , 30 ). AE was shown to be associated with periparasitic accumulation of monocyte-derived M1 macrophages during the early phase of infection, which acquire a M2 phenotype (CD206 + ) during the chronic stage of infection ( 31 , 32 ). These macrophages are considered to favor parasite growth because they secrete the anti-inflammatory cytokine IL-10 and the fibrogenic cytokine TGF-β1, which has a dual role: slowing the parasite growth on one hand, and having immunosuppressive properties on the other ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…AE was shown to be associated with periparasitic accumulation of monocyte-derived M1 macrophages during the early phase of infection, which acquire a M2 phenotype (CD206 + ) during the chronic stage of infection ( 31 , 32 ). These macrophages are considered to favor parasite growth because they secrete the anti-inflammatory cytokine IL-10 and the fibrogenic cytokine TGF-β1, which has a dual role: slowing the parasite growth on one hand, and having immunosuppressive properties on the other ( 32 34 ). Interestingly, we observed in IL-33 −/− mice both a decrease in CD206 + tolerogenic macrophages and lower concentrations of IL-10 and TGF-β1 in the peritoneal cavity, compared to those in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Microglial cells are macrophages derived from the mesoderm and are of two types, M1 and M2, after activation [ 33 ]. M2 microglia polarization is associated with numerous diseases, including cancers, inflammation, and fibrosis diseases [ 30 , 31 , 34 ]. Activated M2 microglia are involved in a series of immune responses, such as phagocytosis of apoptotic and damaged cells [ 35 ], inflammatory responses, and [ 36 ] tissue repair [ 37 ], which play a neuroprotective role.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining was performed as previous described [ 31 ]. BV2 cells were cultured in Dulbecco’s modified Eagle’s medium supplemented with 10% fetal bovine serum and then infected with GFP-tagged LC3 lentivirus (GeneChem, Shanghai, China) according to the manufacturer’s protocol.…”
Section: Methodsmentioning
confidence: 99%
“…MAPK signaling pathway is crucial for parasitic infection ( Zhao et al, 2019 ). Shigui Chong et al found that soluble antigen of Echinococcus multilocularis induces macrophage polarization after alveolar echinococcosis infection through RhoA MAPK signal pathway ( Chong et al, 2022 ). Emmpk1, a host extracellular signal regulated kinase (ERK), could activate parasitic MAPK cascade as it could be phosphorylated by multilocular Echinococcus cysts in vitro ( Hemphill et al, 2002 ; Spiliotis et al, 2006 ).…”
Section: Recent Advances In Drugs From Labmentioning
confidence: 99%